1993
DOI: 10.2307/1494941
|View full text |Cite
|
Sign up to set email alerts
|

Gender Studies and Teacher Education: A Proposal

Abstract: Although gender studies have become a central concern in Canadian universities through women's studies programs or programs in feminist theory, they have not influenced courses and programs in faculties of education to the extent they should. We propose the "mainstreaming" of gender studies and argue that courses and programs should be reconceived and reconstructed to incorporate the findings and approaches developed in feminist and women's studies. We talk of "gender studies" because, unlike "women's studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Despite a global push for gender studies to have a stronger focus in pre-service education (Equal Opportunities Commission 2007; Pearson and Rooke 1993;UNESCO 2003), responses from the interviewees in New Zealand and England indicated that such content had been minimal during their student-teacher days. This was the case even for the men new to teaching.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Despite a global push for gender studies to have a stronger focus in pre-service education (Equal Opportunities Commission 2007; Pearson and Rooke 1993;UNESCO 2003), responses from the interviewees in New Zealand and England indicated that such content had been minimal during their student-teacher days. This was the case even for the men new to teaching.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Pearson and Rooke (1993, 416) asserted that if it “is legitimate to have separate women's courses, it is also appropriate to mainstream core courses” because doing so eliminates “imbalances that are perpetrated by sex role stereotyping and sex biases.” For example, significant numbers of women continue to seek civic jobs, like school board and county clerk positions, that can be perceived as extensions of their gender role, and these stereotypes point to an inherent problem with gender role stratification (Lublin and Brewer 2003; Verba, Schlozman, and Brady 1995). Gender mainstreaming is essential to changing attitudes about gender from the ground up.…”
mentioning
confidence: 99%